2017
DOI: 10.5423/rpd.2017.23.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Resistance to Benzimidazole Fungicides with Mutation of β-Tubulin Gene in Venturia nashicola

Abstract: Pear scab caused by Venturia nashicola has been reported as an important disease of pear resulting in lowering the quality of pear fruits. In this study, it was conducted to investigate the relationship between resistance of V. nashicola and mutation of β-tubulin gene and the fungicide resistance in field isolate group in benzimidazole fungicides. Responce of V. nashicola to carbendazim could be classified into 3 groups as sensitive that does not grow at all on PDA amended with 0.16 μg/ml of carbendazim, low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…If conventional culture methods are not appropriate to monitor fungicide resistance, molecular-based methods might be useful as alternatives for a slow-growing and poor-sporulating fungus like Venturia in particular. The mechanism of MBC resistance was well characterized in V. nashicola [ 10 , 57 ] and various molecular methods such as PCR-RFLP (restriction fragment length polymorphism) analysis and ASPCR (allele-specific PCR) have been developed for the diagnosis of resistance [ 10 ]. However, mechanisms of the DMI resistance are not well known yet.…”
Section: Discussionmentioning
confidence: 99%
“…If conventional culture methods are not appropriate to monitor fungicide resistance, molecular-based methods might be useful as alternatives for a slow-growing and poor-sporulating fungus like Venturia in particular. The mechanism of MBC resistance was well characterized in V. nashicola [ 10 , 57 ] and various molecular methods such as PCR-RFLP (restriction fragment length polymorphism) analysis and ASPCR (allele-specific PCR) have been developed for the diagnosis of resistance [ 10 ]. However, mechanisms of the DMI resistance are not well known yet.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Kwak et al. (2017) reported that mutation of E198A may indicate whether the isolates are resistant to benzimidazole fungicides [26]. It is already known that benzimidazole fungicides bind to fungal TUB2 and inhibit microtubule formation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The partial TUB2 sequence was amplified with primer Btub14F (5′-AACCAAATTGGTGCTGCCTTCTG-3′) and BtubR (5′-TGGAGGACATCTTAAGACCACG-3′) as described by Kwak et al. [26]. The partial TEF-1α sequence was amplified with primer VNEFI-f (5′-ACTTGATCTACAAGTGCGGTG-3′) and VNEFI-r (5′-AGGAGTCTCACTTCCAGAG-3′) as described by Zhao et al.…”
Section: Methodsmentioning
confidence: 99%
“…Benzimidazole fungicides, also known as methyl benzimidazole carbamates, interfere with the formation of the α, β-dimer by binding to the β-tubulin subunit during the microtubule biosynthesis process in fungi ( Davidse and Flach, 1977 ). However, if mutations occur in specific nucleotide sequences of the TUB2 gene, which encodes the β-tubulin protein, benzimidazole fungicides fail to bind to their target, leading to resistance to the fungicidal effects ( Kwak et al, 2017 ; Leroux et al, 2002 ; Yarden and Katan, 1993 ). Specifically, the benzimidazole resistance in B. cinerea has been attributed primarily to a mutation at the 198th codon of the β-tubulin ( Bardas et al, 2008 ).…”
mentioning
confidence: 99%